Efficacy of Polydeoxyribonucleic Acid (PDRN) in periodontal regeneration: A systematic review of clinical outcomes - Ranjith Mari; Jaiganesh Ramamurthy; K. Rudhra; Nitya Krishnaswamy (Journal of Oral Biology and Craniofacial Research)
Background: Periodontal disease is a major dental health concern due to its impact on the supporting structures of teeth, including the alveolar bone and periodontal ligament. Polydeoxyribonucleic Acid (PDRN) has shown promise in promoting tissue regeneration through anti-inflammatory effects and angiogenesis, crucial for periodontal healing. Objective: To evaluate the clinical effectiveness of Polydeoxyribonucleic Acid (PDRN) in periodontal regeneration through a systematic analysis of available studies. Methods: This review followed PRISMA guidelines and included randomized controlled trials (RCTs), cohort, and case-control studies assessing PDRN's effects on periodontal regeneration. A comprehensive search in PubMed, Scopus, Web of Science, and Embase was conducted using keywords related to PDRN and periodontal regeneration. Primary outcomes included clinical attachment level (CAL) gain, probing depth reduction, and bone fill. Two reviewers independently assessed study eligibility and extracted data on PDRN application methods, dosages, and observed outcomes. Results: Among the four studies that met the inclusion criteria, significant improvements in CAL, bone fill, and probing depth reduction were consistently observed in PDRN-treated sites compared to controls. Animal studies also demonstrated enhanced bone quality, reduced inflammation, and a conducive environment for cell proliferation. Clinical trials indicated that PDRN, as an adjunct to conventional therapy, produced more favorable outcomes in periodontal healing. PDRN's activation of adenosine A2A receptors and VEGF expression promoted angiogenesis and modulated inflammatory responses, aiding regeneration. Conclusion: PDRN appears to offer substantial benefits in periodontal regeneration by enhancing bone and tissue healing and reducing inflammatory responses. While promising, further clinical trials are necessary to determine optimal dosing and long-term effectiveness. This systematic review provides evidence supporting PDRN as a potential adjunctive treatment for periodontitis, with implications for enhancing clinical outcomes in periodontal therapy.